Encounters at the end of the world: Max Weber, Carl Schmitt and the Tyranny of Values. Issue 3 (2nd July 2016) - Cerella, Antonio
Abstract : This essay aims at throwing new light on a decades-long controversy over the intellectual relation between Weber and Schmitt. This debate over time has been characterized by polar positions, with the "Weberians" who exclude any continuity between the theorist of Wertfreiheit and the Kronjurist of the Third Reich; and those who not only emphasize similarities, but also a true intellectual filiation between them. Without denying legitimacy to these interpretations, I shall argue that the similarities as well as the differences between Weber and Schmitt are to be found and located in the larger context of the crisis of modernity. Both theorists lived and witnessed the dilemmas caused by the process of rationalization, the neutralization of politics, the technocracy it entailed, and the emergence of a secular polytheism of values. The crisis of modernity – and of political mediation – is the background against which these two thinkers have shaped their conceptual tools but, as I shall explain, the intellectual weapons they used to address this epochal crisis are different. Between the Weberian "ethics of responsibility" and the Schmittian "neutralization of values, " there is an abyss crossed by an ideology: the political.